Method for reducing ESR of laminated aluminum capacitor
Through two impregnation processes and vibration coverage technology, the problem of incomplete silver paste coverage of laminated aluminum capacitors is solved, the ESR is reduced, the production efficiency and qualification rate are improved, and it is suitable for special-shaped designs and high-layer number of aluminum capacitors.
Patent Information
- Application Number
- CN202411531505.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-10
AI Technical Summary
In the case of special-shaped design or high-layer quantity, the incomplete silver paste coverage leads to high ESR, low production efficiency and poor pass rate, and the aluminum core oxide film has high brittleness and poor friction stress resistance, which makes it difficult to meet high Voltage, large capacity, small volume requirements.
Using two impregnation processes, the stack is cured after the first impregnation, and then the second impregnation is performed. The coverage area of silver paste is increased by vibration or non-vibration, the gap between the stacked bodies is filled to form a complete silver paste coating layer instead. Traditional hooking steps.
It achieves good coverage of silver paste on the side and bottom surface of the stacked body cathode, reduces ESR to single-digit mΩ level, improves leakage current pass rate, and has high production efficiency. It is suitable for special-shaped designs and high-layer number aluminum capacitors.
Smart Images

Figure CN119296972A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of aluminum capacitor preparation, and in particular relates to a method for reducing the ESR of a laminated aluminum capacitor. Background Art
[0002] The main process flow of existing multilayer aluminum capacitors is as follows: Figure 3 As shown. Among them, polymerization and impregnation of graphite and silver paste is to generate a conductive polymer on the surface of aluminum foil as a cathode, and then cover the polymer surface with graphite and silver paste in turn to improve the stress resistance of the aluminum core, reduce the contact resistance of the cathode lead layer, improve the cathode lead, and reduce ESR. The hook line is to apply a layer of silver paste on the edge of the stacked aluminum core to establish a closer current conduction path between the stacked layers, thereby reducing ESR. Figure 4 shown.
[0003] The thickness of the anodized aluminum foil used in the laminated aluminum capacitor is 0.100mm to 0.125mm. When immersed in silver paste, due to the effect of surface tension, such as Figure 3 As shown in the figure, the edge of the single-piece aluminum core cannot be completely covered by silver paste. The cathode of the laminated aluminum capacitor is a high molecular conductive polymer with poor stress resistance. The edge is damaged by cutting and is not completely covered by silver paste, becoming a weak point of the product. At the same time, since the edge of the cathode of the single-piece aluminum core is less covered with silver paste, the current on its positive and negative sides mainly relies on the high molecular conductive polymer and graphite for conduction. The conductivity of the high molecular conductive polymer is 10×10 4 S / m, the conductivity of graphite is 1.5×10 4 S / m~2.1×10 4 S / m, the conductivity of silver is 6.3×10 7 S / m, the conduction efficiency of the two is much lower than that of silver, resulting in a large ESR of the laminated aluminum capacitor. It is necessary to coat a layer of silver paste on the cathode edge of the aluminum core stack after lamination to reduce the ESR of the capacitor.
[0004] For multilayer aluminum capacitors with 8 layers or less and a rectangular core design, equipment can be used to draw lines on the bottom of the product. However, for aluminum capacitors with special-shaped core designs, or with rectangular core designs and more than 8 layers, due to the limitations of equipment and silver paste viscosity, the method of using equipment to coat the edge of the aluminum core stack with silver paste can easily cause incomplete silver paste coverage between the layers of the aluminum core stack and at the contact between the aluminum core stack and the lead end. Therefore, for rectangular stacks or special-shaped stacks with more than 8 layers, manual brushing is often used to coat the cathode edge of the product with silver paste. This production method not only leads to low production efficiency and poor product ESR consistency, but also cannot solve the problem of low pass rate caused by poor friction stress resistance of the aluminum core.
[0005] Due to the increasing market demand for high-voltage, high-capacity, and compact laminated aluminum, the design of laminated aluminum products is gradually trending towards more multi-layered structures and featuring unusual shapes. Furthermore, the thick, brittle oxide film of the chemically formed aluminum foil used in high-voltage products has poor resistance to frictional stress, which results in significant damage to the oxide film during capacitor molding. Therefore, manufacturing methods need to be optimized and improved to meet the capacitor's requirements for lower ESR and improved resistance to frictional stress.
[0006] Patent document CN114709081A discloses a high-capacity, low-voltage, chip-type laminated aluminum capacitor and its manufacturing method. The capacitor comprises a housing, wherein multiple cathode waterproof shells are disposed within the housing. A silver-containing cathode layer is disposed within the cathode waterproof shells, which in turn are disposed within a carbon-containing cathode layer. An electrolyte layer is disposed within the carbon-containing cathode layer, and an aluminum foil body is disposed within the electrolyte layer. This invention not only achieves high capacitance, but also withstands high temperatures and reduces the probability of leakage.
[0007] Patent document CN107731531A discloses a mixed polymerization solution, a chip-type solid aluminum electrolytic capacitor, and a mixed polymerization process thereof. The mixed polymerization solution includes a chemical polymerization solution and a dispersed polymerization solution. The mixed polymerization solution is used to produce a uniform, dense conductive polymer layer with strong voltage resistance and low leakage current. The mixed polymerization process of the chip-type solid aluminum electrolytic capacitor is to use a pretreatment solution, a chemical polymerization solution, and a dispersed polymerization solution to perform multiple polymerization treatments on the aluminum foil until a dense and uniform solid electrolyte layer is formed on the surface of the aluminum foil, and then the capacitor is made.
[0008] However, the above invention does not disclose the technical content of increasing the coating area and reducing the ESR by multiple immersion in slurry. Summary of the Invention
[0009] To solve the above technical problems, the present invention provides a method for reducing the ESR of a laminated aluminum capacitor.
[0010] The present invention is achieved through the following technical solutions.
[0011] The present invention provides a method for reducing the ESR of a laminated aluminum capacitor, comprising the following steps:
[0012] S1: The aluminum core is impregnated for the first time;
[0013] S2: stacking the aluminum cores after the first impregnation to obtain a stacked body, and then curing;
[0014] S3: The solidified aluminum core stack is impregnated for the second time.
[0015] Preferably, in step S1, the single-piece aluminum core is impregnated with graphite and silver paste in sequence, and the impregnation method is normal pressure impregnation, and the impregnation can be a vibration or non-vibration impregnation method.
[0016] Preferably, the silver paste impregnation in step S1 is carried out at room temperature. If vibration is added during the impregnation process, the vibration frequency is 25-38 Hz, the amplitude is 1.0-2.0 mm, the impregnation time is 20-40 s, and the extraction speed is 0.01-0.5 mm / s.
[0017] Preferably, the silver paste used for silver paste impregnation in step S1 has a viscosity of 1000-2000 cps and a solid content of 40-90%.
[0018] Preferably, the graphite impregnated in step S1 has a viscosity of 40 to 120 cps, a solid content of 8 to 25%, and an impregnation extraction speed of 0.01 to 0.2 mm / s.
[0019] Preferably, the step of stacking and curing the aluminum cores in step S2 includes: a stacking step: connecting the negative electrodes of the single aluminum cores by bonding silver paste according to the designed number of layers, and connecting the positive electrodes to a carrier such as a lead frame or an aluminum lead by metal mutual melting or using a conductive adhesive;
[0020] Curing step: Measure the thickness of the stacked body, use a flat plate for curing, use a curing pressure of 2.5-4.5N, and cure at 155-165°C for 10-30min.
[0021] Preferably, the shape of the aluminum core stack in step S2 includes a rectangle, a sector and a polygon; the carrier of the aluminum core stack includes a lead frame, a metal bar and a metal lead.
[0022] Preferably, the shapes of the aluminum core stack in step S2 include fan-shaped and polygonal shapes; the stack includes regular-shaped stack and irregular-shaped stack, and the carrier of the aluminum core stack includes a lead frame, metal strips and metal leads.
[0023] Preferably, when the aluminum core stack is rectangular or irregularly shaped, the number of aluminum core stacks may be greater than 8 layers.
[0024] Preferably, the second impregnation liquid in step S3 is silver paste, and the second impregnation includes two steps of impregnation, and the two steps of the second impregnation are dried at ≤ 60°C in between.
[0025] Preferably, the silver paste has a viscosity of 1000 to 2000 cps and a solid content of 40 to 90%. The impregnation method of the first impregnation of the second impregnation includes normal pressure impregnation and negative pressure impregnation, and the pressure is 0 to -60 kPa. The two-step impregnation of the second impregnation can be carried out in a vibration or non-vibration manner. If vibration is used, the vibration frequency is 25 to 38 Hz, the amplitude is 1.0 to 2.0 mm, the impregnation time is 30 to 60 s, and the extraction speed of the two-step impregnation of the second impregnation is 0.01 to 0.5 mm / s.
[0026] The beneficial effects of the present invention are:
[0027] When preparing aluminum capacitors using the aluminum capacitor cathode material prepared by the present invention, the wire drawing step in the prior art can be replaced by secondary impregnation to achieve good coverage of the cathode side and bottom of the stack by silver paste and fully fill the gaps between the cathode layers of the stack.
[0028] The present invention adopts the form of an aluminum core stack to be impregnated with silver paste as a whole. During the impregnation, the side and bottom surfaces are transformed from a cut edge of a single aluminum core to a surface of the stack, thereby achieving complete coating of the side and bottom surfaces of the stack with the silver paste, that is, the edges of the single cores constituting the stack can all be well coated with the silver paste, and at the same time, the gaps between the layers of the aluminum core stack are filled, so that the ESR can be reduced to the single-digit mΩ level, and the aging leakage current qualified rate is significantly improved. This method is convenient for batch operation, the adjustment of the impregnation depth is simple and convenient, and the production efficiency is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic diagram of the silver immersion effect of the aluminum core stack of the present invention;
[0030] Figure 2 It is a schematic diagram of a single piece of aluminum core;
[0031] Figure 3 The process flow of preparing the existing multilayer aluminum capacitor is shown in the figure;
[0032] Figure 4 This is a schematic diagram of the hook line effect of the existing core stack; DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below, but the scope of protection claimed is not limited to the description.
[0034] Example 1:
[0035] like Figure 1 As shown, a method for reducing the ESR of a stacked aluminum capacitor includes the following steps:
[0036] S1: The aluminum core is impregnated for the first time;
[0037] S2: stacking the aluminum cores after the first impregnation to obtain a stacked body, and then curing;
[0038] S3: The solidified aluminum core stack is impregnated for the second time to obtain an aluminum capacitor cathode material.
[0039] The prepared aluminum capacitor cathode material is connected to the positive electrode using an isolation glue to form the main structure of the aluminum capacitor.
[0040] In step S1, a single aluminum core is sequentially impregnated with graphite and silver pastes at atmospheric pressure. The main body of the single aluminum core is aluminum foil, which is coated with a release adhesive. After the first impregnation, the outer surface of the aluminum foil is formed, from the inside out, with a conductive polymer layer, a graphite layer, and a silver paste layer. The conductive polymer layer is prepared by a conventional polymerization process.
[0041] In step S1, the silver paste impregnation is carried out at room temperature, and vibration is added during the impregnation process, with a vibration frequency of 25 Hz, an amplitude of 1.0 mm, an impregnation time of 20 s, and an extraction speed of 0.01 mm / s.
[0042] The silver paste used for silver paste impregnation in step S1 has a viscosity of 1000 cps and a solid content of 40%.
[0043] The graphite impregnated in step S1 has a viscosity of 40 cps, a solid content of 8%, and an impregnation extraction speed of 0.01 mm / s.
[0044] The step of stacking and solidifying the aluminum cores in step S2 includes: a stacking step: connecting the negative electrodes of the single aluminum cores by bonding silver paste according to the designed number of layers, and connecting the positive electrodes by metal mutual melting, specifically laser welding, to connect the lead frame, aluminum lead and other carriers together;
[0045] Curing steps: Measure the thickness of the stacked body, select a gasket with a thickness of ±0.1 mm for the measured thickness for positioning, use a flat plate with a pressure sensor for curing, use a curing pressure of 2.5 N, and cure at 155° C. for 10 minutes.
[0046] In step S2, the aluminum core stack is rectangular in shape, the carrier of the aluminum core stack is a lead frame, and the number of aluminum core stack layers is 9.
[0047] The second impregnation liquid in step S3 is silver paste, and the second impregnation includes two impregnation steps. The two impregnation steps of the second impregnation are dried at ≤60°C in between. The purpose of the first impregnation step of the second impregnation is to fill the gaps between the stacking layers with silver paste, and the drying time is 10 to 60 minutes. The purpose of the second impregnation step of the second impregnation is to form a complete silver paste coating layer with a certain thickness in the cathode area of the stacking body.
[0048] The silver paste has a viscosity of 1000 cps and a solid content of 40%. The first step of the second impregnation is impregnation at normal pressure. The two-step impregnation of the second impregnation adopts a vibration method with a vibration frequency of 25 Hz, an amplitude of 1.0 mm, and an impregnation time of 30 s. The extraction speed of the two-step impregnation of the second impregnation is 0.01 mm / s.
[0049] Example 2:
[0050] A method for reducing the ESR of a laminated aluminum capacitor comprises the following steps:
[0051] S1: The aluminum core is impregnated for the first time;
[0052] S2: stacking the aluminum cores after the first impregnation to obtain a stacked body, and then curing;
[0053] S3: The solidified aluminum core stack is impregnated for the second time to obtain an aluminum capacitor cathode material.
[0054] The prepared aluminum capacitor cathode material is connected to the positive electrode using an isolation glue to form the main structure of the aluminum capacitor.
[0055] In step S1, a single aluminum core is sequentially impregnated with graphite and silver pastes at atmospheric pressure. The main body of the single aluminum core is aluminum foil, which is coated with a release adhesive. After the first impregnation, the outer surface of the aluminum foil is formed, from the inside out, with a conductive polymer layer, a graphite layer, and a silver paste layer. The conductive polymer layer is prepared by a conventional polymerization process.
[0056] In step S1, the silver paste impregnation is performed at room temperature, the impregnation time is 40 seconds, and the extraction speed is 0.5 mm / s.
[0057] The silver paste used for silver paste impregnation in step S1 has a viscosity of 2000 cps and a solid content of 90%.
[0058] The graphite impregnated in step S1 has a viscosity of 120 cps, a solid content of 25%, and an impregnation extraction speed of 0.2 mm / s.
[0059] The step of stacking and solidifying the aluminum cores in step S2 includes: a stacking step: connecting the negative electrodes of the single aluminum cores by bonding silver paste according to the designed number of layers, and connecting the positive electrodes by metal mutual melting, specifically resistance welding, to connect the lead frame, aluminum lead and other carriers together;
[0060] Curing steps: Measure the thickness of the stacked body, select a gasket with a thickness of ±0.1 mm for the measured thickness for positioning, use a flat plate with a pressure sensor for curing, use a curing pressure of 4.5 N, and cure at 165°C for 30 minutes.
[0061] In step S2, the shape of the aluminum core stack is fan-shaped; the carrier of the aluminum core stack is a steel bar.
[0062] The second impregnation liquid in step S3 is silver paste, and the second impregnation includes two impregnation steps. The two impregnation steps of the second impregnation are dried at ≤60°C in between. The purpose of the first impregnation step of the second impregnation is to fill the gaps between the stacking layers with silver paste, and the drying time is 60 minutes. The purpose of the second impregnation step of the second impregnation is to form a complete silver paste coating layer with a certain thickness in the cathode area of the stacking body.
[0063] The viscosity of the silver paste is 2000cps, the solid content is 90%, the impregnation method of the first step of the second impregnation is negative pressure impregnation, the pressure is -60kpa, the two-step impregnation of the second impregnation adopts a vibration method, the vibration frequency is 38Hz, the amplitude is 2.0mm, the impregnation time is 60s, and the extraction speed of the two-step impregnation of the second impregnation is 0.5mm / s.
[0064] Example 3:
[0065] like Figure 1 As shown, a method for reducing the ESR of a stacked aluminum capacitor includes the following steps:
[0066] S1: The aluminum core is impregnated for the first time;
[0067] S2: stacking the aluminum cores after the first impregnation to obtain a stacked body, and then curing;
[0068] S3: The solidified aluminum core stack is impregnated for the second time to obtain an aluminum capacitor cathode material.
[0069] The prepared aluminum capacitor cathode material is connected to the positive electrode using an isolation glue to form the main structure of the aluminum capacitor.
[0070] In step S1, a single aluminum core is sequentially impregnated with graphite and silver pastes at atmospheric pressure. The main body of the single aluminum core is aluminum foil, which is coated with a release adhesive. After the first impregnation, the outer surface of the aluminum foil is formed, from the inside out, with a conductive polymer layer, a graphite layer, and a silver paste layer. The conductive polymer layer is prepared by a conventional polymerization process.
[0071] In step S1, the silver paste impregnation is carried out at room temperature, and vibration is added during the impregnation process, with a vibration frequency of 30 Hz, an amplitude of 1.5 mm, an impregnation time of 90 s, and an extraction speed of 0.03 mm / s.
[0072] The silver paste used for silver paste impregnation in step S1 has a viscosity of 1600 cps and a solid content of 60%.
[0073] The graphite impregnated in step S1 has a viscosity of 70 cps, a solid content of 16%, and an impregnation extraction speed of 0.01 mm / s.
[0074] The step of stacking and curing the aluminum cores in step S2 includes: a stacking step: connecting the negative electrodes of the single aluminum cores by bonding silver paste according to the designed number of layers, and connecting the positive electrodes by metal mutual melting, specifically by using a conductive adhesive to connect with a carrier such as a lead frame and an aluminum lead;
[0075] Curing steps: Measure the thickness of the stacked body, select a gasket with a thickness of ±0.1 mm for positioning, use a flat plate with a pressure sensor for curing, use a curing pressure of 3.5 N, and cure at 160°C for 20 minutes.
[0076] In step S2, the aluminum core stack is rectangular in shape, the carrier of the aluminum core stack is a metal lead, and the number of aluminum core stack layers is 9.
[0077] The second impregnation liquid in step S3 is silver paste, and the second impregnation includes two impregnation steps. The two impregnation steps of the second impregnation are dried at ≤60°C in between. The purpose of the first impregnation step of the second impregnation is to fill the gaps between the stacking layers with silver paste, and the drying time is 30 minutes. The purpose of the second impregnation step of the second impregnation is to form a complete silver paste coating layer with a certain thickness in the cathode area of the stacking body.
[0078] The viscosity of the silver paste is 1500cps, the solid content is 70%, the impregnation method of the first step of the second impregnation is negative pressure impregnation, the pressure is -60kpa, the two-step impregnation of the second impregnation adopts a vibration method, the vibration frequency is 30Hz, the amplitude is 1.6mm, the impregnation time is 45s, and the extraction speed of the two-step impregnation of the second impregnation is 0.2mm / s.
[0079] Comparative Example 1: Existing CD55-F1-40V-75μF aluminum capacitor prepared using the line drawing step.
[0080] A CD55-40V-75μF-F1 aluminum capacitor was prepared using the aluminum capacitor cathode materials prepared in Examples 1-3. The capacitor was then tested against the CD55-F1-40V-75μF aluminum capacitor from Comparative Example 1. The test conditions were: capacitance and loss at 100Hz frequency and 2V bias voltage; ESR at 100kHz frequency and 2V bias voltage; and DC leakage current at rated voltage and 300s. The test results are shown in the table below.
[0081]
[0082] It can be seen from the above table that the aluminum capacitors produced by the silver immersion method of this method have better parameters, higher qualified rate, and lower ESR.
Claims
1. A method for reducing the ESR of a laminated aluminum capacitor, characterized in that: The following steps are involved: S1: The aluminum core is impregnated for the first time; S2: stacking the aluminum cores after the first impregnation to obtain a stacked body, and then curing; S3: The cured aluminum core stack is impregnated for the second time.
2. A method for reducing the ESR of a laminated aluminum capacitor as claimed in claim 1, characterized in that: In the step S1, the single-piece aluminum core is impregnated with graphite and silver paste in sequence, and the impregnation method is normal pressure impregnation, and the impregnation can be a vibration or non-vibration impregnation method.
3. A method for reducing the ESR of a laminated aluminum capacitor as claimed in claim 2, characterized in that: In step S1, the silver paste impregnation is carried out at room temperature. If vibration is added during the impregnation process, the vibration frequency is 25-38 Hz, the amplitude is 1.0-2.0 mm, the impregnation time is 20-40 s, and the extraction speed is 0.01-0.5 mm / s.
4. A method for reducing the ESR of a laminated aluminum capacitor as claimed in claim 2, characterized in that: The silver paste used for silver paste impregnation in step S1 has a viscosity of 1000-2000 cps and a solid content of 40-90%.
5. A method for reducing the ESR of a laminated aluminum capacitor as claimed in claim 2, characterized in that: The graphite impregnated in step S1 has a viscosity of 40-120 cps, a solid content of 8-25%, and an impregnation extraction speed of 0.01-0.2 mm / s.
6. A method for reducing the ESR of a laminated aluminum capacitor as claimed in claim 1, characterized in that: The step of stacking and curing the aluminum cores in step S2 comprises: Stacking steps: According to the designed number of layers, the negative electrode of the single aluminum core is connected by bonding silver paste, and the positive electrode is connected to the lead frame or aluminum lead carrier by metal mutual melting or conductive adhesive; Curing step: measure the thickness of the stack, use a flat plate for curing, the curing pressure is 2.5-4.5N, and the curing temperature is 155-165°C for 10-30min.
7. A method for reducing the ESR of a laminated aluminum capacitor as claimed in claim 1, characterized in that: In step S2, the shapes of the aluminum core stacks include sectors and polygons; the stacks include regular-shaped stacks and irregular-shaped stacks, and the carriers of the aluminum core stacks include lead frames, metal strips and metal leads.
8. A method for reducing the ESR of a laminated aluminum capacitor as claimed in claim 7, characterized in that: When the aluminum core stack is in a rectangular or irregular shape, the number of aluminum core stacks may be greater than 8 layers.
9. A method for reducing the ESR of a laminated aluminum capacitor as claimed in claim 1, characterized in that: In step S3, the second impregnation liquid is silver paste, and the second impregnation includes two steps of impregnation. The two steps of the second impregnation are dried at ≤ 60° C. between the two steps, and the drying time is 10 to 60 minutes.
10. A method for reducing the ESR of a laminated aluminum capacitor as claimed in claim 9, characterized in that: The silver paste has a viscosity of 1000-2000 cps and a solid content of 40-90%. The first step of the second impregnation includes normal pressure impregnation and negative pressure impregnation, and the pressure is 0--60 kpa. The two-step impregnation of the second impregnation can be carried out in a vibrating or non-vibrating manner. If vibrating, the vibration frequency is 25-38 Hz, the amplitude is 1.0-2.0 mm, the impregnation time is 30-60 s, and the extraction speed of the two-step impregnation of the second impregnation is 0.01-0.5 mm / s.
Citation Information
Patent Citations
Mixed polymerization solution, chip-type solid aluminum electrolytic capacitor and mixing-type polymerization technique thereof
CN107731531A
High-capacity low-voltage chip-type laminated aluminum capacitor and preparation method thereof
CN114709081A